Integrating Information and Communication Technologies Into Second and Foreign Language Teaching: Pedagogical Benefits and Considerations - Mai, Nguyen Thanh (VNU Journal of Science: Education Research; Vol 36 No 4DO - 10.25073/2588-1159/vnuer.4401, 2020)
The article aims to review existing literature on the pedagogical benefits as well as considerations regarding the integration of Information and Communication Technologies (ICTs) into second and foreign language teaching. Greater collaboration and interaction, enhanced motivation and access to a huge repository of web-based materials are among the most popular advantages of ICTs. At the same time, ICT-integration into language teaching can be challenging due to the emergence of “multiliteracies” and the not-so-ICT-competent students in the language classroom. Besides, there are language teachers who fear that their professional identity could be disrupted as they try to adopt new technologies in their teaching. However, the review also points out that technologies do not automatically result in any remarkable pedagogical benefits without teachers’ selective use. It is the teachers who enlarge the potentials of ICTs in promoting meaningful interactions and real intercultural reflections beyond the conventional language classrooms.